Análise transcriptômica da interação de abacaxizeiro com o Pineapple mealybug wilt-associated virus - Peron, Fernanda Nunes (2018)
Ananas comosus var comosus is a fruit of great economic and nutritional value worldwide. The productivity of the pineapple crop is influenced by mealybug wilt of pineapple (MWP). This disease is caused by Pineapple mealybug wilt-associated virus (PMWaV), the PMWaV-1 and PMWaV-2 variants are associated with the symptoms of the disease. The symptoms derive from the atrophy of the roots followed by wilting and discoloration of the leaves with redness and consequent deficiency in fruiting. The control of the disease occurs by the removal of symptomatic plants is not satisfactory especially since infected asymptomatic plants serve as a source of virus dispersion through their seedlings. Therefore, in this work, the differential transcriptome between symptomatic and asymptomatic infected plants was evaluated by RNA-seq, bioinformatic tools and RT-qPCR to propose an understanding of the pathogenesis of MWP under field conditions. Additionally, the proteins were confirmed by mass spectrometry analysis. Based on the reference genome of Ananas comosus, 16,097 expressed genes were identified, 268 repressed and 122 induced. The performance of RNA-seq was confirmed for 14 expressively expressed genes (DEGs) with a satisfactory Pearson correlation (R = 0.788). Functional classification and enrichment analysis revealed induction of genes involved in the regulation of flowering while repressed genes were predominantly related to the defense mechanisms of abiotic and biotic stress. Among them, some transcription factors (FT) WRKYs and MYBs, PRs, HSPs, AQPs and genes encoding ROS-removing enzymes, and Copper, Calcium and Zinc transporters were repressed. On the other hand, the expression of auxin responsive genes was positively regulated by ARFs. We observed hormonal regulation mediated by inhibition of jasmonate biosynthesis (JA), induction of ethylene biosynthesis (ET) and induction of the expression of genes responsive to auxin, what was related to the development of symptoms. A protein-protein interaction network was predicted allowing the visualization of the interaction of the gene products of the DEGs. Therefore, it was possible to observe the grouping of chaperones in the center of the network. We confirmed the inhibition of expression of the genes encoding the ERDJ3B, BiP2 and RTM2 chaperones in symptomatic plants and identified a significant negative correlation (R = -0.715) between the levels of RTM2 and PMWaV-2 transcripts. As the expression of this virus is predominant in symptomatic plants, we propose RTM2 as a probable gene associated with PMWaV-2 dispersion control. In addition, an HSP20 protein was identified only in asymptomatic plant samples reinforcing the hypothesis of HSP20 involvement in infection control. In the same way, we identified the HSP70, CaM and CRT proteins. These proteins had the repressed gene expression in the symptomatic plants pointing to stress in the endoplasmic reticulum (ER) as a response to PMWaV infection. Because viruses require the cellular machinery, we believe that pineapple plants suppress the expression of resident chaperones in the UPR (unfolfed protein response) as a strategy to limit the pathogen at the site of infection. However, with the introduction of SAR (systemic acquired resistance) and RTM2 expression, possible barriers to the displacement of PMWaV-2 were suppressed. In addition, the IRE1 expression reveals the activation of UPR to cell death by apoptosis. Thus, it is surprisingly concluded that PMWaV-2 infection elicits a hypersensitive response through UPR, in addition to modulating R gene expression.In view of the above, this thesis contributes to the revision of the methods adopted for the management of MWP both in cultural practices and the level of genetic improvement of pineapple.